2020
DOI: 10.22190/fupes200114006m
|View full text |Cite
|
Sign up to set email alerts
|

Motor Skills of Soccer Players Aged 16-18 in Regard to Competition Level and Playing Position

Abstract: TThe aim of this paper was to examine the differences in the motor skills of soccer players aged 16-18 years who play in different competition levels (National League and Regional League), as well as players who play in different positions in the team. The standard testing battery for the motor skills assessment of soccer players was used to evaluate the motor skills. As for the evaluation of the differences between the different playing positions, a two-factor ANOVA with the factor Competition Level (National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Based on this study, it can be concluded that agility is an extremely complex ability, as other authors have a similar view (Bloomfield et al, 1994;Buttifant et al, 2002;Bangsbo & Mohr, 2012), and its connection to other skills and performance components is hard to define (Sheppard & Young, 2006;Koltai et al, 2016), so it is significance for soccer is quite immense (Radák, 2019). The agility tests AWB or AWOB belong to motor tests organically in the case of young soccer players (Momčilović et al, 2020). their relation with other abilities and the performance component structure are quite difficult to define.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, it can be concluded that agility is an extremely complex ability, as other authors have a similar view (Bloomfield et al, 1994;Buttifant et al, 2002;Bangsbo & Mohr, 2012), and its connection to other skills and performance components is hard to define (Sheppard & Young, 2006;Koltai et al, 2016), so it is significance for soccer is quite immense (Radák, 2019). The agility tests AWB or AWOB belong to motor tests organically in the case of young soccer players (Momčilović et al, 2020). their relation with other abilities and the performance component structure are quite difficult to define.…”
Section: Discussionmentioning
confidence: 99%